2017
DOI: 10.1177/1971400917744885
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery and stereotactic radiotherapy with cyberknife system for meningioma treatment

Abstract: Objective The aim of this work was to evaluate the impact of stereotactic radiosurgery/fractionated stereotactic radiotherapy with the Cyberknife system on local disease control, clinical outcome and toxicity in patients with meningioma, according to the site and histological grade of lesion. From January 2013 to April 2017, 52 patients with intracranial meningiomas were treated with the Cyberknife system. Twenty-four patients had undergone previous surgery: 38% gross total resection, 10% subtotal resection; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
0
18
0
3
Order By: Relevance
“…The CyberKnife system allows for the delivery of 6 MV photons for radiotherapy via an image-guided radiosurgical treatment platform with a frameless robotic manipulator and 6D Skull Tracking system to highly conformal intracranial high-dose tumor targeting, with sub-millimeter precision beam delivery and steep dose gradients achievable around the contoured target volume [11,12,15]. These advantages have allowed CKRT to be a feasible option for patients who are not considered suitable for surgery or cannot tolerate frame-based RT.…”
Section: Indications For Using Cyberknife Radiation Therapy For the Tmentioning
confidence: 99%
See 3 more Smart Citations
“…The CyberKnife system allows for the delivery of 6 MV photons for radiotherapy via an image-guided radiosurgical treatment platform with a frameless robotic manipulator and 6D Skull Tracking system to highly conformal intracranial high-dose tumor targeting, with sub-millimeter precision beam delivery and steep dose gradients achievable around the contoured target volume [11,12,15]. These advantages have allowed CKRT to be a feasible option for patients who are not considered suitable for surgery or cannot tolerate frame-based RT.…”
Section: Indications For Using Cyberknife Radiation Therapy For the Tmentioning
confidence: 99%
“…SRT (HRST and FSRT) delivered at lower doses over several fractions can be used for tumors that are within close proximity to critical neurovasculature structures to achieve tissue sparing of radiation-associated adverse events [7,8]. In addition, SRT can be used to treat large OGMs (> 10 cm 3 ) that may be in close proximity to the optic apparatus [8,11,18,21]. In our case series, 4 patients with smaller sized OGMs within close proximity to the optic chiasm and 4 patients with larger OGMs with a median tumor volume of 10.1 cm 3 were treated with SRT.…”
Section: Indications For Using Cyberknife Radiation Therapy For the Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, auditory function is also not commonly reported on in radiotherapy series, with more focus on tumor control and adverse radiation effects. Di Franco et al 13 reported on the use of the Cyberknife for the treatment of meningiomas with a mix of SRS and fractionated stereotactic radiotherapy (FSRT) cases. A single fraction was used to treat lesions less than 2 cm, while FSRT was used to treat lesions greater than 2 cm or less than 3 cm, but too close to a critical site, such as the optical chiasm or CPA.…”
Section: Radiotherapy and Hearingmentioning
confidence: 99%